Provision of facilities for people with disabilities provided at local parks in Ipoh, Perak - Mohamad Nazri, Muhammad Naqib Najhan (2024)
The research, titled "Provision of Facilities for People with Disabilities Provided at Local Park in Ipoh, Perak," aims to determine whether the local recreational parks in Ipoh, Perak comply with the Universal Design guideline for Local Recreational Parks regarding the facilities provided for people with disabilities (PwDs). The purpose of the findings is to highlight areas that require improvement and provide useful data regarding how well the current facilities are complied with Universal Design guidelines for Local Recreational Park. Promoting equal participation and enjoyment for all members of the community, including those with disabilities. This research seeks to determine the range of facilities accessible to people with disabilities (PwDs) at these parks, as well as their actual availability and condition. Additionally, the research will explore the extent to which these facilities comply to Universal Design Guidelines for Local Recreational Park. Through the use of direct observation, the research allows for a comprehensive and methodical evaluation of the condition of on-site facilities. In addition to identifying particular difficulties and constraints faced by PwDs in accessing and using these outdoor spaces, this method offers a thorough overview of the current situation regarding accessibility at the local parks in Ipoh, Perak.